Shift work: overall health state related to sleep in nursing workers - Mendes, Sandra Soares; Martino, Milva Maria Figueiredo De (Revista da Escola de Enfermagem da USP, 2012)
The objective of this study was to identify the symptoms related to the overall health status associated with shift work in nursing and relate it to the quality of sleep. The study was performed at Hospital da Irmandade da Santa Casa in Poços de Caldas, Minas Gerais State. The participants were 136 nursing professionals, of an average age of 33.1 years, divided into the following categories: nurse (8.1%); nurse technician (80.9%); and nursing aides working the day and night shifts (11%). The health symptoms were identified based on the Overall Health Status Inventory, and quality of sleep was evaluated based on sleep logs. The Chi-Square test showed statistical significance (p=0.021) for the presence of flatulence and abdominal distension during the night shift. Multiple linear regression analysis revealed that subjects working the day shift who experienced symptoms of poor digestion (sometimes or always) and irritability (always) had a poorer quality of sleep.